Marketing ambiental: consciência econômica x consciência ecológica - Andrade, Laura Lanna (2004)
The study intends to cover the changes that happened on the environmental speech pronounced by the society and companies in the last years. On the present time we still believe in the dichotomy between the environment and capitalism, this way the concepts become excludeiy and bringing a situation that is difficult to solve. Neverthless, there is a new perception that considers these two concepts as complements, searching for a balance between their interests. Keeping that in mind, it's necessary to comprehend when the environmental variable changed to be considered as a market variable, not being faced as an extra cost anymore to become a new business opportunity. Besides that, it's necessary to investigate what influenced and estimulated the business sector to search for new environmental proposals, in other words, if the companies are really searching for new proposals or they are just divulging shallow projects. Analising the results that carne through the analyse of the environment projects, we can perceive that the economical variable is an important factor that motivated the companies to look for the environmental subject path, transforming it in a market variable, a differential showed by some vanguard companies.